Batch study of glycerol decomposition in one-stage supercritical production of biodiesel - Aimaretti, Nora Rosa (2009)
The objective of this work was to assess some of the points that need to be elucidated in order to define the economic viability of the noncatalytic supercritical biodiesel process. Net yield of the supercritical process, consumption of methanol, and the quality of the fuel issuing from the reactor were studied. Biodiesel was prepared by reacting refined soy oil with supercritical methanol at T ) 280 C and methanol-to-oil molar ratios of 15 and 20. After the reaction, unreacted methanol, water, and other volatile compounds were removed from the product by stripping with nitrogen at 110 C. Biodiesel production by the reaction of oils in supercritical methanol under the conditions used in this work produces practically no glycerol byproduct. This fact simplifies the downstream refining of the produced biodiesel. Glycerol is transformed into products of smaller molecular size and water. At first this water reacts with the triglycerides of the reacting mixture to form free fatty acids (FFA), thus increasing the acidity of the product. At longer reaction times the acids are converted into methyl esters again. Glycerol methanolysis reactions increase the methanol consumption. The small amount of glycerides and FFA contaminants in the biodiesel product makes a final step of refining by silica adsorption convenient. No liquid effluents are issued with such a refining step. After the FFA and glycerides are recycled, the yield of the process is 94-96.